Pirates don't wear pink sunglasses - Dadey, Debbie; Jones, Marcia Thornton; Gurney, John Steven, 1962- (New York : Scholastic, 1994)
The Bailey kids suspect the camp director at Camp Lone Wolf is a werewolf and the boat instructor, Captain Teach, is a pirate in search of buried treasure.
"A Little Apple paperback."
640
Accelerated Reader AR
Keywords: Bailey School Kids (Fictitious characters) -- Fiction; Pirates -- Fiction; Schools -- Fiction